Genotoxicity evaluation of the insecticide imidacloprid on circulating blood cells of Montevideo tree frog Hypsiboas pulchellus tadpoles (Anura, Hylidae) by comet and micronucleus bioassays - Ruiz de Arcaute, Celeste (2014)
Acute toxicity and genotoxicity of imidacloprid (IMI) was evaluated on Hypsiboas pulchellus (Anura: Hylidae) tadpoles exposed under laboratory conditions. A lethal effect was used as the end point for lethality, whereas the frequency of micronuclei (MNs) and DNA single-strand breaks evaluated by the single cell gel electrophoresis assay were employed as end points for genotoxicity. Experiments were performed on tadpoles at stage 36 (range, 35–37) according to the classification proposed by Gosner. Mortality studies revealed an LC50 (96 h) value of 84.91 mg/L IMI (95% confidence limits, 77.20–93.04). While increased frequency of MNs was observed when 15 and 30 mg/L were assayed for 48 h, only 15 mg/L increased the frequency of MNs in tadpoles exposed for 96 h. Furthermore, other nuclear abnormalities, i.e., binucleated cells and blebbed and notched nuclei, were induced in tadpoles exposed for both 48 h when treated with 15 mg/L and 96 h when treated with 15 and 30 mg/L. An increase in the genetic damage index was observed in tadpoles treated with 30 mg/L for 48 and 96 h. This study represents the first evidence of acute lethal and sublethal effects exerted by IMI on tadpoles of an amphibian species native to Argentina. Finally, our findings highlight the hazardous properties of this insecticide for nontarget living species exposed to this agrochemical.